The Manjanguak Tradition: Social Learning, Character Education and Psychological Effects - Sukma, Dina (International Journal of Research in Counseling and Education, 2020)
The "manjanguak" tradition is a series of funeral ceremonies held at the funeral home which is attended by family and relatives. The study of the manjanguak tradition is more concerned with the social values contained in it such as value of character education. This is because the manjanguak tradition is a tradition that exists in the human social realm that contains character education values. However, there has not been much discussion of its influence on the individual psychological aspects of this tradition. Humans are social creatures that are closely related to their environment. Humans who are detached from social ties will experience mental health problems such as low self-esteem and low self-control. Therefore, this article is a literature review that discusses all the dimensions contained in the manjangauak tradition. This article focuses not only on the social learning process and the values of character education, but also on the individual psychological effects of the manjanguak tradition.